Encyclopedia of Family Studies 2016
DOI: 10.1002/9781119085621.wbefs344
|View full text |Cite
|
Sign up to set email alerts
|

Feminist Perspectives on Families

Abstract: Feminist perspectives offer a revolutionary critical lens for studying families and for challenging traditional understandings of sex, gender, sexualities, conceptualizations of families, and individuals' family roles. Feminist thought considers issues of power on individual, relational, familial, institutional, structural, and global levels, as well as the interplay of power across these levels. Praxis (i.e., applying research to promote social justice), reflexivity (i.e., critical questioning of research pra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Feelings of feminist fraudulence are largely a by‐product of divergent feminist paradigms and the large number of midlevel theories available for feminist scholars to choose from to guide their scholarship (Lather, ; Sharp & Blume, in press). Our philosophical and theoretical struggles have been primarily embedded in two key challenges that Allen et al () identified: (a) advances in interdisciplinary theorizing and (b) intersectionality.…”
Section: Accounting For Feminism In Our Research: Epistemology Agendmentioning
confidence: 99%
See 1 more Smart Citation
“…Feelings of feminist fraudulence are largely a by‐product of divergent feminist paradigms and the large number of midlevel theories available for feminist scholars to choose from to guide their scholarship (Lather, ; Sharp & Blume, in press). Our philosophical and theoretical struggles have been primarily embedded in two key challenges that Allen et al () identified: (a) advances in interdisciplinary theorizing and (b) intersectionality.…”
Section: Accounting For Feminism In Our Research: Epistemology Agendmentioning
confidence: 99%
“…Allen () reminded us that the epistemological terrain is always shifting, and more recently, scholars have conceptualized epistemological paradigms by identifying positivist, postpositivist, social constructionist and interpretative, critical, and postmodern positions (Daly, ; Lather, ), although these classifications are contested (Mumby, ). Feminist family scholars select from multiple (sometimes incompatible) paradigms by incorporating ideas gleaned from feminist thought in women's studies, where postmodern sensibilities have prevailed for the past several decades, and, within family studies (and social sciences in general), where positivism and postpositivism remain pervasive (Sharp & Blume, in press; Sharp, Zvonkovic, Humble, & Radina, ; Walker, ). That being said, these struggles may be increasingly complex now: More than ever before, greater numbers of epistemological paradigms and feminist theories exist (Allen et al, ).…”
Section: Accounting For Feminism In Our Research: Epistemology Agendmentioning
confidence: 99%
“…Problematizing assumptions of equality, fairness, and well-being in marriage and other family relationships, especially as they disadvantage women” (p. 208). Moreover, feminist theories have offered critical insights within family science through the following: centering gender as site of analysis, challenging binaries and restrictive familial gendered roles, and questioning notions such as families are unmitigatedly safe for its members and that nuclear families are optimal (Allen et al, 2009; Sharp & Blume, 2016).…”
mentioning
confidence: 99%
“…Praxis, or the application of research and theory for social justice, is a distinguishing feature of feminisms (Sharp & Blume, in press) and is highlighted by Sharp and Weaver as a means for creating feminist accountability. The nature of this praxis is further detailed in tables in their article with specific practices for creating more responsible feminist research and for managing feelings of fraudulence.…”
mentioning
confidence: 99%
“…The article by Sharp and Weaver begins with the question, “Are our studies feminist enough?” While I appreciate this epistemological query, it provokes two considerations. First, the authors acknowledge their use of empiricist, standpoint, and postmodern epistemologies across their research projects and a desire to use more critical paradigms; however, also articulating the specific “lens” brought to this particular paper might be more helpful for deconstructing feminist fraudulence, given the wide range of feminist theoretical camps (e.g., liberal, radical, Marxist, postcolonial, environmental, postmodern) (for full descriptions, see Sharp & Blume, in press; Tong, ). Doing so might also help reduce their expressed angst over the “authenticity” and “unknowability” of feminism and help disempower their emotional response.…”
mentioning
confidence: 99%